(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The article offers experimental hypotheses for a participatory management of genetic biobanks understood as common goods, considering the characteristics of genetic data and balancing technocratic tendencies of research with participatory instances of donors in the activity of the biobank. In particular, two models are proposed: external participation with the power of intervention and internal participation or self-management.